Biological Parameters, Environmental Effects, Dispersal Behaviour And Toxicological Studies Of The Tropical Bed Bug, Cimex Hemipterus (Fabricius) (Hemiptera: Cimicidae) - How , Yee Fatt (2010)
This thesis describes the biology, environmental effects, and dispersal behavior of the tropical bed bug, Cimex hemipterus (Fabricius), as well as the toxicological effects of eight insecticides (lambda-cyhalothrin, bifenthrin, fenitrothion, fipronil, imidacloprid, indoxacarb, chlorantraniliprole and DDT) on this species. Tesis ini meliputi kajian mengenai beberapa aspek penting mengenai pepijat, Cimex hemipterus, termasuk biologi, keberkesanan persekitaran, perilaku penyebaran dan juga kajian toksikologi dengan menggunakan Iapan racun serangga (cyhalothrin, bifenthrin, fenitrothion, fipronil, imidacloprid, indoxacarb, chlorantraniliprole dan DDT). Kebangkitan infestasi pepijat kebelakangan taburan dan pengawalannya juga dibincang.